The Influence of Motivation, Work Experience and Employee Empowerment on Employee Performance at Bumi Dipasena Abadi, Lampung - Riefsty Febrianty (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The aim of this study was to determine the effect of motivation on the performance of shrimp farmers in Bumi Dipasena Abadi Lampung, the effect of work experience on the performance of shrimp farmers in Bumi Dipasena Abadi Lampung, the effect of employee empowerment on the performance of shrimp farmers in Bumi Dipasena Abadi Lampung. From the research that has been done, it can be seen that the variable motivation has a positive and significant effect on employee performance at Bumi Dipasena Abadi, Lampung. This means that with the motivation provided by the company, of course this will increase the enthusiasm of the employees at work. The Work Experience Variable has a positive and significant effect on Employee Performance at Bumi Dipasena Abadi, Lampung. This means that with the work experience employees have, they can minimize work errors that cause company losses. The Employee Empowerment Variable has a positive and significant effect on Employee Performance at Bumi Dipasena Abadi, Lampung. This means that with good employee empowerment, it will also have a good impact on employee performance, because companies can evaluate the work of their employees and provide training.